Social media influencer marketing to build a counter-narrative for promoting sexuality education. (20th October 2021) - Ahmed, F; Ahmad, G; Schumacher, J; Brand, T
Abstract: Background: A recent cross sectional community readiness assessment carried out in Islamabad, Pakistan indicated that the community is at the denial or resistant stage for implementing school-based sexuality education in Pakistan. The resistance was attributed to lack of awareness and prevalent misconceptions regarding sexuality education. This study aims at qualitatively exploring strategies for targeting misconceptions and increase awareness regarding sexuality education with stakeholder involvement. Methods: 35 in-depth interviews and a focus group discussion was conducted to discuss the results of the readiness assessment comprising of community members, researchers, NGO representatives, and social media influencers. Discussion guide included topics on engagement strategies, intervention modes of delivery, target audience, misconceptions, community support, and optimizing sexuality education in local context. Qualitative content analysis was conducted for analyzing the data. Results: Results indicate that current community support is usually passive in nature and digital or social media platforms are mostly used to talk about sexuality education. Participants believed social media can be used as a platform for disseminating information by involving social media influencers with careful narrative building around sexuality for rebranding the topic, as talking about sexuality is seen as a taboo in the society. Targeting misconceptions through counter narratives and scientific evidence was considered as a way forward for increasing community acceptability and readiness. Violence, staying safe, and age appropriateness were identified as some of the key features of sexuality education that need to be highlighted for garnering community support. Conclusions: For promoting sexuality education in Pakistan, it is essential to tackle resistance by sensitizing the community and digital social media platforms offer an opportunity to do this through influencer marketing. Key messages: Digital and social media offer an opportunity for promoting sexuality education in conservative settings like Pakistan. Social media influencer marketing might be useful in building counter narrative and for community engagement.